The Effect of Psychological Self-Defence on the Performance of Graduates Employed in Matched and Mismatched Roles - Getrude Cosmas; Patricia Joseph Kimong; Wanda Kiyah George Albert (LUMEN Publishing, 2023)
In today’s competitive job market, most graduates face obstacles in obtaining a job that matches their field and educational level. The lack of jobs related to graduates’ fields and educational levels and to industrial demand in the era of postmodernism has caused psychological tension among graduates. This study predicts that employed graduates who apply mature defence mechanisms show higher work performance compared to graduates who apply immature styles of psychological defence mechanisms. The study also predicts that graduates in matched positions tend to use mature defence mechanisms compared to graduates with job mismatches. To explore this phenomenon, 116 employed graduates from different academic backgrounds shared their views on using mature and immature coping mechanisms in their work performance. The study found that mature self-defence had a positive effect on work performance, while immature defence mechanisms did not show any effect on work performance. Concerning the use of mature and immature defence mechanisms in graduates with matched and mismatched employment, the study revealed that there is no difference between the two groups of graduates in using both types of psychological self-defence. The findings showed that the mature psychological defence mechanisms can be used to understand the factors that contribute to work performance. This can serve as guidance for employed graduates to better perform in their work. For employers, the findings can help them understand their employees’ psychological self-defence in dealing with work challenges in today’s world.